The Oxford handbook of higher education in the Asia-Pacific region - Kapur, Devesh, 1959-; Kong, Lily; Lo, Florence; Malone, David, 1954- (Oxford handbooks., 2023)
With three of the world's largest economies, Asia is poised to home half of the world's middle class-both the driver and the product of higher education. This handbook presents country case-studies and explores cross-cutting trends to offer an understanding of higher education achievements, failings, potential, and limitations in the region.